Legal mechanisms to reduce the level of non-compliance with judgments issued by the Inter-American Court of Human Rights against Peru - Quiñones Montaño, Gabriella (2025)
Compliance with judgments issued by the Inter-American Court of Human Rights is a binding international obligation for Peru under the American Convention on Human Rights. However, current regulations have limitations that affect their effectiveness. The provisions enshrined in the New Constitutional Procedural Code present problematic aspects, and Law No. 27775 does not regulate suitable mechanisms, nor is it properly coordinated with the Regulations of Legislative Decree 1326. In this context, this qualitative research, based on a critical review of case law and national and international legislation, confirmed that the problem lies in the impossibility of operating an enforcement system that lacks precise rules, defined standing, and effective judicial oversight. Therefore, it is proposed to amend the aforementioned regulations in order to establish an effective enforcement procedure and greater regulatory consistency, which will provide legal certainty, regulatory hierarchy, and binding force to the decisions of the Inter-American Court of Human Rights within the national legal system.